Spatial Multifractal and b Value Characteristics of Mine Earthquakes under High Tectonic Stress. (11th April 2022) - Ji, Hongguang; Chen, Dongsheng; Su, Xiaobo; Fu, Zhen; Quan, Daolu
Abstract : Mining-induced earthquake is one of the common risk factors affecting the safety of mining engineering. In order to reveal the information characteristics of mine seismicity and predict the high-energy mine seismicity, based on the microseismic monitoring data of 250105 working face in Huating Coal Mine, the spatial multifractal and magnitude-frequency distribution relationship of mine seismicity activity are analyzed. It was found that under high tectonic stress, the spatial multifractal characteristics of mine seismicity are obvious, and the magnitude-frequency distribution satisfies the Gutenberg-Richter law. There is a positive linear correlation between the fractal dimension D 2 and b value, and the spatial distribution of mine seismicity is correlated with the magnitude-frequency distribution. In terms of D ∞ and D 2 -D ∞, the seismic aggregation degree and fractal structure uniformity are discussed, respectively, and the parameter variation is related to rock burst events. The variations of D 2 and b values are strongly correlated with the main earthquake. The descending gradient of b value and D 2 is the largest in the region where the main shock occurred, and the b value and D 2 take on lower values. The significant decrease of b value and D 2 can be regarded as the precursor feature of the main shock.